Pseudoleptonema tansoongnerni new species (Hydropsychidae: Trichoptera) with species list of Trichoptera from Li Phi Falls, Mekong River, southern Laos - Laudee, Pongsak; Malicky, Hans (Zootaxa, 2017)
A new species named Pseudoleptonema tansoongnerni n. sp. is presented along with a list of Trichoptera from Li Phi falls, Mekong River, southern Laos. Pseudoleptonema tansoongnerni n. sp. is described and figured based on adult males and females. It is distinguished from the others by its forewing pattern and color, which is yellowish brown.